Integrating ERP and enterprise social software. Issue 1 (3rd February 2017) - Greasley, Andrew; Wang, Yucan
Abstract : Purpose: The purpose of this paper is to explore the use of a hybrid enterprise resource planning (ERP) system, combining an ERP system with enterprise social software (ESS). The study will provide a critical assessment of the implementation of this process technology. Design/methodology/approach: Multiple case studies of organisations based in China were conducted to understand the use of ERP systems in different contexts. Following an evaluation of the context of each ERP implementation (within-case analysis) the research draws a cross-case conclusion that defines the nature of a hybrid ERP system and then synthesises the propositions related to the benefits and challenges of implementation. Findings: The authors find that a hybrid ERP system is able to support efficiency in business process management and also provide a flexible response to changes in business requirements. It does this by allowing for the continued use of informal processes that cannot be incorporated into the ERP system. Practical implications: This research indicates how ERP systems in conjunction with ESS can provide a flexible response to changing business requirements and increase collaboration within the organisation. Key lessons include the need to perform informal activities under the guidance of managers and provide clear boundaries for the implementation of informal activities. Originality/value: This study has found that the use of case studies can provide a valuable insight into the use of a hybrid ERP system from the perspective of its use within the organisation as a work system that requires an assessment of the context within which organisational members perform their work.